Boron clusters (ferrabisdicarbollides) shaping the future as radiosensitizers for multimodal (chemo/radio/PBFR) therapy of glioblastoma - Nuez-Martínez, Miquel (2022)
Funding Information: The authors received support from the Spanish Ministerio de Economía y Competitividad (PID2019-106832RB-100), the Generalitat de Catalunya (2017SGR1720), FCT - Fundação para a Ciência e a Tecnologia, in the scope of the projects LISBOA-01-0247-FEDER-045904, and the project LA/P/0140/2020 of the Associate Laboratory Institute for Health and Bioeconomy - i4HB. The Metrology Laboratory of Ionizing Radiation team of Centro Tecnológico e Nuclear, Instituto Superior Técnico (CTN/IST) is acknowledged for their support in the irradiation setups. Miquel Nuez-Martínez is enrolled in the PhD program of the UAB. MQM and VMA acknowledge financial support by the Spanish Government MCIN/AEI/10.13039/501100011033 (project 2019-108434GB-I00 to VMA and project IJC2018-035283-I to MQM), and Universitat Jaume I (project UJI-B2018-53 to V. M. A. and project UJI-A2020-21 to MQM). SV thanks Croatian Science Foundation (project IP-2018-01-3168). Catarina I.G. Pinto is enrolled in the PhD scholarship 689 DFA/BD/07119/2020. Publisher Copyright: © 2022 The Royal Society of Chemistry.